Cyberloafing Behaviors in Students’ Learning Process: EFL Teachers’ Efforts to Create Productive Learning Environment - Dyah Kusumastuti,; Purwanto,; Saputra, Indra (Journal of Language and Literature Studies, 2024)
The phenomenon of cyberloafing, where individuals engage in non-work-related online activities during productive hours, has become increasingly prevalent, particularly among students. This study investigates the impact of cyberloafing on students' learning processes, aiming to fill a research gap in understanding its effects on academic performance and classroom dynamics. A quantitative descriptive approach was employed to gather data through a questionnaire completed by 69 students selected via simple random sampling. To complement the quantitative data, qualitative insights were obtained from interviews with five randomly selected students. The survey explored the frequency and nature of cyberloafing activities, variables promoting such behavior, and its impacts. Analysis of the questionnaire data revealed that students engage in cyberloafing more frequently during classroom activities than during informational or leisure activities. Many students perceive cyberloafing as a means to alleviate classroom boredom. Interview findings indicated mixed outcomes: while some students reported reduced tension and boredom, others did not perceive any benefits and even noted a decline in productivity and focus. This study contributes to the existing body of knowledge by highlighting the dual nature of cyberloafing's impact. While it can serve as a coping mechanism to mitigate boredom and stress, it also has the potential to detract from academic performance. Understanding these dynamics can help educators and policymakers develop strategies to manage cyberloafing, promoting a more balanced and productive learning environment.